Prokaryotic microbial compositions and physicochemical characteristics of Huangshui, a by-product of Baijiu fermentation - TANG Yanping, GAO Xiubing, NI Jie, ZHANG Fengqin (Zhongguo niangzao)
Huangshui is a by-product of solid-state fermentation Baijiu that has abundant microbial resources. In this study, the similarities and differences in physicochemical properties and prokaryotic microbial structures among different sources of Huangshui were comprehensively analyzed by physicochemical detection methods and high-throughput sequencing technology. The results showed that pH, total acid, non-volatile acid, alcohol content, reducing sugar and starch contents of Huangshui in different workshops were highly significantly different (P<0.01), and there were significant differences in the diversity, richness and structural composition of Huangshui prokaryotic microbial communities in different workshops (P<0.05). Lactobacillus was the dominant genus of all prokaryotic microorganisms, and its relative abundance ranged from 72.34% to 98.52%, which was positively correlated with the contents of total acid, alcohol content, non-volatile acid and starch content. The Huangshui contained Weissella, Enterococcus and Parabacteroides, which were positively correlated with pH and reducing sugar content. In addition, the differences of Huangshui prokaryotic microbial communities in different workshops affected the contents of acids and esters in base liquor, and Lactobacillus had a highly significant positive correlation with the contents of total acids and total esters (P<0.01). The difference of community structure of Huangshui prokaryotic microorganisms in different workshops was significantly correlated with physicochemical factors. Understanding the effects of physicochemical factors on prokaryotic microorganisms could provide a data for screening functional strains using Huangshui as raw materials. Physicochemical factors significantly affected the community composition of prokaryotic microorganisms in Huangshui, and the differences in community structure of prokaryotic microorganisms in different workshops were significantly related to physicochemical factors.